Syria's widening protests : Assad increasingly beleaguered - James M. Dorsey (2012)
The protests against Syrian president Bashar al Assad’s regime is spreading to the country’s business community and middle-class residents of Damascus. There is also mounting international pressure on Assad to halt the crackdown while the US and EU prepare to impose new sanctions on Syrian oil exports.